Character Education: Analysis of Self-Regulated Learning on Systems Online Learning during the Covid-19 Pandemic - Triana Kartika Santi; Riztika Widyasari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The temporary closure of all educational institutions as an effort to prevent the spread of the Covid-19 outbreak worldwide has an impact on millions of students, including in Indonesia. The distance learning process (Online) is a learning solution during the pandemic which in its implementation has not been optimal as a whole. This adds to the obstacles in the application of learning methods because on one occasion there are too many learning loads that must be overcome by the teaching staff. This Writing Method Using descriptive. The main source of self-regulated formation is internal, meaning that it depends on the individual's actions, not on what other people do self-regulated formation is also inseparable from external factors, namely the environment. One study found that people with low self-regulation often experience negative emotions from people with high self-esteem. This can be interpreted that individuals will try to find symbols that can provide positive experiences and acceptance of a good environment. Online learning uses materials and timescales that are following the curriculum. The online learning method is here to change the conventional teaching style which can later improve work professionalism. Self-Regulation is a major influence on the formation of the character of students so that in achieving the formation of student character it is necessary to have Self-Regulated oriented learning. Character education during the pandemic is very different from its application in the conventional period because all learning is all digital (Online), therefore it is very difficult for students and lecturers to organize self-regulated learning processes. Character education is hampered by its value because student self-regulation is not organized, and affects student learning outcomes.